RIO (Antimicrobial) - Protective Door / Amirah Husna Abd.Latiff and Norarifah Ali - Abd.Latiff, Amirah Husna; Ali, Norarifah (Faculty of Art and Design, 2021)
In 2020, we are shocked by the pandemic that is spreading around the world, namely Covid-19. Covid-19 easily spreads through exposed surfaces such as in public places. When a person lacks or does not practice hygiene and does not wash his hands often is more susceptible to infection. When we go to a public place, the thing we always touch is the door handle. Doors that often have handles are available at stores such as petrol stations, marts, offices, shopping malls and more. When we are in a public place, frequent contact with the door handle contributes to high risk of spreading the infection, quoted from an article from Veena Babulal on 18 September 2020 entitled “Sceptical of outdoor sanitisation”. Infection control expert Dr Tengku Zetty Maztura Tengku Jamaluddin confirmed that the chemicals and their concentrations administered by the authorities, which were recognized by the World Health Organization (WHO), have the capability of killing the virus effectively. The solution (concentration) is between low and medium strength, but even mild solution can deactivate and kill SARS-CoV-2, “refers to the Covid-19 causing virus, which can live for hours on porous surfaces, such as cupboards, three or four days on plastic and stainless steel, and up to seven days on discarded face masks. With this hook, the user only uses hand sanitation when necessary because it has provided protection to the user.